Assessment of Cavitation Activity by Cavitation Noise in Different Frequency Ranges - V. S. Minchuk; A. Y. Perhunova; M. P. Fedorinchik; N. V. Dezhkunov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of testing the spectral-acoustic cavitometer with measurement modes that differ in the frequency ranges of integration of cavitation noise are presented. For each of the H1–H4 modes, the lower integration frequency  fmin is 1, 70, 180 and 300 kHz, respectively. The upper frequency is the same for all modes and  is   fmax  =  10  MHz. Piezoelectric waveguide sensors were used as a cavitation noise receivers. The distributions of cavitation activity in non-uniform ultrasonic fields were recorded: in the volume of the ultrasonic bath  (f0 = 35 kHz) and in the field of the submersible emitter (f0 = 21 kHz). The frequency range of integration was varied by changing the lower bound. It has been established that a change in the integration range within a fairly wide range does not have a noticeable qualitative effect on the result of measurements of cavitation activity, only a multiple change in the readings occurs. This conclusion was confirmed using sensors that differ in their spectral characteristics.